(untitled) - Lefauve, Adrien (Comptes Rendus. Physique, 2024)
Geophysical fluid flows that are stably-stratified in density, like most of the ocean, can be strongly turbulent at small scales as a result of shear instabilities. The resulting mixing controls the vertical transport of heat and tracers that are key to large-scale layering and circulation patterns, including those crucial to Earth’s climate. However, the physics of sheared stratified turbulence remain poorly understood due to their extraordinary range of scales and spatio-temporal intermittency. This paper reviews a laboratory model, the stratified inclined duct (SID), which encapsulates these fundamental physics and complexity while permitting precise control and measurements, a sweet spot to stimulate fruitful research. We explain how this exchange flow down a modest slope sustains high levels of energy dissipation and mixing while remaining strongly-stratified, thereby accessing the relevant geophysical parameter regime. Emphasising the role of detailed measurements, we highlight key discoveries and unsolved questions around the transition to turbulence, intermittent dynamics and parameterisations of mixing. Dimensional design guidelines show how the optical measurements of the full three-dimensional flow field could be perfected to extrapolate laboratory results to the tantalisingly close regime of the most intense geophysical stratified turbulence.